Keterkaitan Kesehatan Spiritual (Spiritual Well-Being) Dan Orientasi Keputusan Etis (Ethical Orientation Of Decision Making) (Studi Empiris terhadap Para Pembuat Keputusan di Indonesia Tahun 2016) - I Cenik Ardana; Elizabeth Sugiarto D; Yuniarwati Yuniarwati (Jurnal Akuntansi, 2017)
Specifically, the purpose of this studyis: (1)totest thevalidity and reliabilityofthemeasurement modelofFisher'sspiritualwell-being (SWB)construct(2010);(2) to testthevalidity  and  reliabilityofthemeasurement  modelofForsyth’sethicalorientation  ofdecision-making(EDM)construct(1980),  and  (3)toexamine  thecorrelationof  Fisher’sSWBvariables   withForsyth’sEDMvariables(1980).   Testing    instruments   ormeasurement  models    usesconfirmatory  factor  analysis  and  Cronbach  Alpha's  reliabilityandtestingcorrelationusesPerlson'scorrelation. The dataisprocessed with SPSS version22.  The  results  of  this  study  showed  that:  (1)  the  measurment  modelofFisher’sSWBconstructis  valid  and  reliable;  (2)  the  measurment  model  of  Forsyth’sEDMconstruct  isalsovalid  and  reliable.It  is  also  concluded  that  there  is  a  positive  and  significantcorrelation  betweenidealspiritualwell-being  (ISWB)construct,  either  in  whole  (ISWB)and each dimension (ICSWB,  IPSWB,  ITSWB,  IESWB)with ideal  ethical orientationofdecision-making  (IEDM).  There  is  also  a  positive  and  significant  relationship  betweenlivedspiritualwell-being (LSWB)constructas a whole withrelativeethicalorientation ofdecision-making (REDM). In testing thecorrelationof each dimensionofLSWBconstruct(LCSWB, LPSWB, LTSWB, LESWB)withREDMconstruct, despite all the dimensionsofLSWB  shows  positivecorrelationswith  REDM,  but  the  level  ofsignificance  oftheassociation varies.